Cohesive strength of zirconia/molybdenum interfaces and grain boundaries in molybdenum: A comparative study. (15th August 2017) - Lenchuk, Olena; Rohrer, Jochen; Albe, Karsten
Abstract: We present calculations within density functional theory on the thermodynamic stability and mechanical properties of t-ZrO2 (001)/Mo(001) interfaces. The interfacial strength is evaluated by applying energy-based (work of separation) and stress-based (theoretical strength) criteria for different cleavage planes. The lowest energy for crack propagation is obtained for a cut creating a stoichiometric ZrO2 (001) surface. Our results reveal that molybdenum grain boundaries contaminated with oxygen are less stable against brittle fracture than pure Mo GBs. Addition of Zr, however, can strengthen Mo grain boundaries that contain oxygen by forming an ultrathin zirconia film between Mo grains. The stress required to cleave an ultrathin zirconia film is equal to that required for a pure Mo GB.